Efektivitas Program pada Pelayanan Publik E-Parking di Taman Bungkul Kota Surabaya - Murdyastutik, Anastasia; Prasetya, Herjuna Anandita; Supranoto, Supranoto (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
This study aims to describe the level of program effectiveness in e-parking publik services at Taman Bungkul Surabaya City which was launched by the Surabaya City Government through the Surabaya City Transportation Service. E-parking is an e-government program launched with the hope of being able to meet the needs of the people of Surabaya in the parking sector. The reason underlying this research is that the Surabaya City Government answers various parking problems that are complained by the community by implementing a technology-based parking service program, namely parking meters. With this parking meter, he hopes to be able to provide solutions to parking problems in the city of Surabaya. Therefore, there are indications of wasting the regional budget (APBD) if this program does not run in accordance with what the Surabaya City government wants. This study uses a descriptive method with a quantitative approach. Respondents in this study amounted to 100 people. The sampling technique used is incidental sampling technique. In this study, researchers used 4 (four) data collection techniques, namely questionnaires, observation, interviews and documentation. The data obtained were then tested for validity through the product moment correlation test using the SPSS 26 application, then the data that were declared valid were presented and analyzed. The data analysis technique in this study uses frequency distribution. The data evidence is in the form of respondent's questionnaires, photos, and also interview transcripts. Based on the research results, it is known that the e-parking service program implemented by the Surabaya City Transportation Service is declared effective. Based on the results of the calculation of the frequency distribution, it shows significant results that the implementation of the e-parking service program is in the Good category with a total frequency of 47% with a total of 47 respondents. Based on the results of calculations carried out in measuring the effectiveness of the e-parking service program in the city of Surabaya, it can be concluded that it is effective or in the good category